2021
DOI: 10.1007/s00404-021-06134-3
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of urinary incontinence from first childbirth to 30-months postpartum

Abstract: Purpose The objectives of this study were to determine the incidence of UI in a large cohort of primiparous women before and during pregnancy and over the course of 30 months postpartum, and to identify risk factors for UI during and after pregnancy. Methods Nulliparous women aged 18 to 35 years with singleton pregnancies were interviewed in their third trimester and asked about urinary incontinence before and during pregnancy (n = 3001). After delivery these women were interviewed at 1, 6, 12, 18, 24 and 30 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…Previous studies showed that the incidences of abnormal pelvic floor functions and UI in postpartum women were (50–64%) and (23–32%), respectively, which were basically consistent with our results ( Qi et al, 2019 ; Yang et al, 2019 ; Patel et al, 2021 ). In this study, we concluded that more than half of (69.4%) postpartum women 6–8 weeks after delivery had abnormal pelvic floor functions, while the incidence of urinary incontinence UI was sharply lower (23.0%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies showed that the incidences of abnormal pelvic floor functions and UI in postpartum women were (50–64%) and (23–32%), respectively, which were basically consistent with our results ( Qi et al, 2019 ; Yang et al, 2019 ; Patel et al, 2021 ). In this study, we concluded that more than half of (69.4%) postpartum women 6–8 weeks after delivery had abnormal pelvic floor functions, while the incidence of urinary incontinence UI was sharply lower (23.0%).…”
Section: Discussionsupporting
confidence: 93%
“…However, there were more risk factors for postpartum women with urinary incontinence. Considering that urinary incontinence is a symptom of severe pelvic floor dysfunction, the correlation of risk factors is more pronounced than symptomless women, but researches have so far proved inconclusive results about which factors (age, weight, delivery type, and fetal weight) wielded more influences on pelvic floor functions and the occurrence of UI ( Qi et al, 2019 ; Blomquist et al, 2020 ; Li et al, 2020 ; Fu et al, 2021 ; Patel et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was a secondary analysis of a cross-sectional study of sexual dysfunction in participants who gave birth by any method (cesarean, spontaneous vaginal, or operative vaginal delivery) in the past 3 years. This period was chosen because recent data suggest that issues that may arise in the peripartum period, including incontinence, may persist for much longer than 1 year after delivery 5,13 . Qualtrics XM (Seattle, WA), an online survey platform, was engaged to recruit and survey 600 participants in Ohio, Pennsylvania, and Michigan to evaluate sexual function after birth.…”
Section: Methodsmentioning
confidence: 99%
“…This period was chosen because recent data suggest that issues that may arise in the peripartum period, including incontinence, may persist for much longer than 1 year after delivery. 5,13 Qualtrics XM (Seattle, WA), an online survey platform, was engaged to recruit and survey 600 participants in Ohio, Pennsylvania, and Michigan to evaluate sexual function after birth. Qualtrics leverages multiple sample sources to recruit populations that are challenging to recruit otherwise, such as minority populations and those who may not be comfortable discussing certain conditions in a clinical setting; surveys are administered electronically via email.…”
Section: Methodsmentioning
confidence: 99%
“…Urinary incontinence, or the involuntary leaking of urine, becomes more likely in the third trimester. An estimated 37% of women experience urinary incontinence during pregnancy and it is most common in the third trimester [24]. Running and jumping will increase the incidence of urinary incontinence during pregnancy as it significantly increases the stress on the pelvic floor [2] which is already undergoing increased stress from the weight of the uterus and growing fetus.…”
Section: The Third Trimestermentioning
confidence: 99%